2018
DOI: 10.1177/1742271x17748515
|View full text |Cite
|
Sign up to set email alerts
|

Fetal adrenal gland biometry and cervical elastography as predictors of preterm birth: A comparative study

Abstract: The elastographic advancement and fetal adrenal biometry derived quantitative markers can be used as an objective and standard criterion for accurate prediction of preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
1
42
1
1
Order By: Relevance
“…This finding could be attributed to the pathologic nature of the cervical stroma, which is mainly composed of fibromuscular tissue, which is less dense than myometrium. To our knowledge, no previous examined SWE for the normal cervix, although there are multiple studies on the role of elastography, including strain elastography and acoustic radiation force impulse imaging, in the cervix for labor assessment and predicting preterm birth …”
Section: Discussionmentioning
confidence: 99%
“…This finding could be attributed to the pathologic nature of the cervical stroma, which is mainly composed of fibromuscular tissue, which is less dense than myometrium. To our knowledge, no previous examined SWE for the normal cervix, although there are multiple studies on the role of elastography, including strain elastography and acoustic radiation force impulse imaging, in the cervix for labor assessment and predicting preterm birth …”
Section: Discussionmentioning
confidence: 99%
“…The ratio between the fetal zone and the whole adrenal gland could accurately distinguish between patients with symptoms of preterm birth who delivered within the next week and those who did not with high sensitivity and specificity [15]. The groups of Santipap et al as well as Agarwal reported that in patients with either threatened preterm labour or preterm labour an enlarged adrenal gland in combination with high levels of placental alpha macroglobulin-1 or cervical elastography respectively was effective in predicting preterm delivery within 7 days [17,18]. The adrenal gland ratio was reported to be independent of gestational age [9] and is therefore particular useful for screening.…”
Section: Introductionmentioning
confidence: 99%
“…Two approaches for cervical ultrasound elastography for quantitative determination of the physical properties of the cervix, namely, strain elastography and shear wave elastography have been developed. We identified 11 clinical studies in the last three years, which tested the hypothesis that cervical elastography may be useful in predicting preterm delivery [20]- [25] [34] [35] [36] [37] [38]. Of the eleven studies identified, seven used strain ultrasound [20]- [25] [35] and four used shear wave ultrasound [34] [36] [37] [38].…”
Section: Discussionmentioning
confidence: 99%